Twentyseventh Meeting of the National Development Council March 21 and 22, 1970 Summary Record - Planning Commission (Planning Commission, 1970)
Welcoming the members of the National Development Council. Shrimati INDIRA GANDHI. Prime Minister expressed her appreciation of the hard work put in by the Deputy Chairman and Members of the Planning Commission in an exceedingly difficult situation. She added that Deputy Chairman would give a detailed analysis of the resources of the Plan and the lines on which it had been recast. Since the last meeting of the National Development Council, many changes had taken place. The relationship between the Centre and the States and between the Slates themselves had assumed an even greater importance.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Union Territories; National Development Council; Finance Commission; Draft Fourth Plan; Central industrial projects; The Chief Minister; common denomination; Himachal Pradesh; Mobilisation; Nationalisation